2008
DOI: 10.1177/0145445507309030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex, Gender Role Identification, and Gender Relevance of Two Types of Stressors on Cardiovascular and Subjective Responses

Abstract: The authors tested the hypothesis that a match between the gender relevance of a stressor and one's sex or gender role identification would elicit higher cardiovascular responses. Healthy female and male undergraduates (n = 108) were exposed to two stressors: the Cold Pressor Test (CPT) and the n-back task. Stressor relevance was manipulated to be masculine or feminine relevant or gender neutral. Data were analyzed using a Bayesian model selection procedure. The results showed stronger cardiovascular responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
1
21
1
Order By: Relevance
“…One is because it could partially explain why CV response correlates of gender have been inconsistent in stress, health and other performance challenge studies (Atienza, Henderson, Wilcox, & King, 2001;Brown & Smith, 1992;Davis & Matthews, 1996;Jorgenson & Houston, 1981;Lash, Eisler, & Schulnian, 1990;Lash, Gillespie, Eisler, & Southard, 1991;Leinwand, 2003;Matthews, Davis, Stoney, Owens, & Caggiula, 1991;Stoney, Matthews, McDonald, & Johnson, 1988;Saab et al, 1997;Smith, Limon, Gallo, & Ngu, 1996;Stroud, Niaura, & Stoney, 2001;Van Egeren, 1979;Van Well, Kolk, & Klugkist, 2008). Most often, investigators have observed stronger CV responses in men, with effects being especially likely for systolic blood pressure (SBP -Saab, 1989;Stoney, Davis, & Matthews, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…One is because it could partially explain why CV response correlates of gender have been inconsistent in stress, health and other performance challenge studies (Atienza, Henderson, Wilcox, & King, 2001;Brown & Smith, 1992;Davis & Matthews, 1996;Jorgenson & Houston, 1981;Lash, Eisler, & Schulnian, 1990;Lash, Gillespie, Eisler, & Southard, 1991;Leinwand, 2003;Matthews, Davis, Stoney, Owens, & Caggiula, 1991;Stoney, Matthews, McDonald, & Johnson, 1988;Saab et al, 1997;Smith, Limon, Gallo, & Ngu, 1996;Stroud, Niaura, & Stoney, 2001;Van Egeren, 1979;Van Well, Kolk, & Klugkist, 2008). Most often, investigators have observed stronger CV responses in men, with effects being especially likely for systolic blood pressure (SBP -Saab, 1989;Stoney, Davis, & Matthews, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps not surprisingly, the resulting findings are inconsistent. For example, although some studies show that social support benefits women and not men (e.g., Matud, Carballeira, López, Marrero, & Ibáñez, 2002), others show that social support benefits men but not women (e.g., van Well, Kolk, & Klugkist, 2008), and still others find that social support operates similarly for women and men (e.g., Cheng & Chan, 2006;Flaherty & Richman, 1989;van Daalen et al, 2005). In the present study, we attempt to move this literature forward by using a large, homogeneous sample and a multidimensional assessment of support.…”
mentioning
confidence: 99%
“…In contrast to the gender-match effect found for the cold pressor test, the memory task evidenced stronger cardiovascular responses for a gender-mismatch introduction. The investigators hypothesized that in accordance with prior theory on the topic (Tomaka 1993) the active nature of the memory task tapped challenge appraisal from participants, whereas the passive nature of the cold pressor test is more likely to elicit threat appraisal (van Well et al, 2008). Their results highlight the influence of gender on situational appraisal and subsequent physiological responses, and also highlight the need to either control for this confound in stress research or to conduct specific gender analyses.…”
Section: Primary Pathways Associated With Sex and Gender Differencmentioning
confidence: 95%
“…In such gender role studies, the gender orientation of a stress task is manipulated by tailoring the language of the introduction to the task to reference either masculine role, feminine role, or gender neutral role. One study examined the effect of gender role matching on cardiovascular stress responses following two tasks, the cold pressor test and a task that included memory testing, in 108 men and women (van Well et al, 2008). Gender relevance was manipulated by tailoring the introduction of the stressors in the following ways.…”
Section: Primary Pathways Associated With Sex and Gender Differencmentioning
confidence: 99%
See 1 more Smart Citation